John. A Haywood, Manual of the Laws of North-Carolina 199-200 (1808) - (:unkn) unknown (My University, 1768)
Hunting, § 2: From and after the First day of January next, no person whatever (masters excepted) not having a freehold of one hundred acres of land within this province, or tending ten thousand corn hills, at least five feet distance each, shall hunt or kill deer, under the penalty of ten pounds proclamation money for every offence;
Keywords: HUNTING REGULATION